Antecedent of Private University Lecturers’ Participation and E Learning Platforms - Leonnard Ong (Publikasi Indonesia, 2025)
The aim of the study is to explore the relationship between e-learning platform preferences and lecturers’ participation on e-learning. Data were collected using questionnaires distributed to 59 lecturers of a university. The questionnaire showed that there is a difference in the e-learning tools, techniques or platforms used by the lecturers. The results of chi square test shows that there was no significant relationship between e-learning platform preference and technical quality, learners and lecturers participaton. In addition, low level of lecturers participation depends significantly only on learners participation, while technical quality, support system quality and educational support quality did not show any significant causal relationship. Further discussion and research are needed in order to gain more dimensions of lecturers’ perspective.